Publication of Notices in a Procurement Procedure - Dobra, Emalita (European Journal of Multidisciplinary Studies, 2016)
The Contract Notice is an extremely important part of the procurement process. It marks the commencement of the formal procurement process for a specific contract and notifies potential economic operators of the concrete opportunity to participate in the procurement process. To ensure as much competition as possible and to comply with the basic requirements for transparency, the Contract Notice must be drafted in a way that clearly describes the nature, scope and estimated value of the contract and how economic operators can apply to participate in the process. The Contract Notice must also be completed fully and correctly. Failure to draft a clear, complete and compliant Contract Notice could result in a disappointing level of competition, poor quality or inappropriate tenders, or a flawed procurement process that might have to be re-started. In cases when there is a need for correction or changing of the contract notice and all the subsequent information, another notice should be published. This implies a requirement to notify all potential tenderers of any revision so as not to favor one tenderer in particular. In any case, it is important to consider carefully the impact of any changes that the contracting authority proposes to refer to in the amending notice. There are no specified minimum and maximum time periods for publishing a Contract Notice, but there are statutory time limits that start on the date of dispatch of the Contract Notice